Biodiesel Synthesis From Waste Cooking Oil Using CaO.SrO Catalyst By Transesterification Reaction In Batch Reactor - Widiarti, Nuni; Haq, Ismi Arinal; Mahatmanti, F. Widhi; Harjito, Harjito; Kurniawan, Cepi; Suprapto, Surapto; Prasetyoko, Didik (Universitas Negeri Semarang, 2018)
CaO is a very good catalyst for oil transesterification reactions into biodiesel, but requires a reaction time of 2 hours to obtain equilibrium. The time of CaO catalysis reaction can be accelerated by modifying the CaO catalyst with SrO. Synthesis biodiesel of waste cooking oil has been successfully conducted by transesterification reaction that used batch reactor assisted by CaO.SrO catalyst. The aim of this study is to determine the characteristics and catalytic activity of catalyst in the transesterification reaction. Catalysts have been successfully synthesized by coprecipitation method with oil to methanol molar ratio of 1:1, and its calcined at 800oC for 3 hours. Catalyst was characterized by XRD to determine the crystallinity. The smaller catalyst crystallinity obtained as the decline in intensity and shifts diffraction angles of CaO modified SrO catalyst. Surface area of catalyst characterized by SAA, that allow surface area between CaO modified SrO by 10.217 m2/g. Transesterification reaction performed on variation time (30, 60, 90, 120, 150 minutes), and the catalysts amount (1, 2, 4, 6, 8% w/v). The optimum condition of catalytic activity in reaction for 2 hours and the catalyst amount is 1% w/v of reactants that produce yield of biodiesel is 96.4%.